The phoQ gene of Pseudomonas plecoglossicida influences the immune response in Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ during infection - Meiqin Mao; Li He; Xiangyang Lin; Jianshao Wu; Zhixia Zhuang; Xiaoru Wang; Huabin Huang; Qingpi Yan (Aquaculture Reports)
Pseudomonas plecoglossicida can cause visceral white spot disease in various species of teleost fish, leading to significant economic losses in the aquaculture industry. The PhoP/PhoQ two-component system plays a crucial role in regulating bacterial virulence and maintaining internal environmental balance. In this study, hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) was used as a model to compare the pathogenic differences between the phoQ gene knockout strain (ΔphoQ), the phoQ gene complement strain (C-ΔphoQ), and the wild-type strain (NZBD9). Additionally, transcriptome sequencing was employed to explore the impact of phoQ gene deletion on the host immune response during P. plecoglossicida infection. The results showed that the cumulative survival rate of the ΔphoQ infection group was 10 % higher than that of the NZBD9 group, with significantly reduced bacterial load in the spleen and less tissue damage. Transcriptomic analysis revealed that, compared to the NZBD9 infection group, the ΔphoQ infection group induced 4453 differentially expressed genes, which were enriched in several immune-related pathways according to GO and KEGG analysis. These pathways included 22 immune system pathways, 28 signal transduction pathways, and 9 cell growth and death pathways. Further qRT-PCR analysis confirmed that phoQ gene deletion affected the expression of several immune- and inflammation-related genes, such as IL-1β, IL-6, CD3, C8, CCL2, MHC-II, PGRP6, and SLP2. Particularly during the infection process, the expression level of the PGRP6 gene in the ΔphoQ strain infection group was significantly higher than that in the NZBD9 strain infection group, suggesting that PGRP6 may be involved in the host's immune recognition of P. plecoglossicida. In conclusion, the phoQ gene plays an important role in the pathogenesis of P. plecoglossicida infection in hybrid grouper. The deletion of the phoQ gene significantly affects the pathogenicity of P. plecoglossicida and enhances the host’s immune response, providing a theoretical basis for the potential application of the PhoP/PhoQ system in the immune defense of aquatic animals.